Extraneous Cognitive Load as a Moderator of the Correlation Between Mathematical Literacy and Mathematical Reasoning in Indonesian Junior High School Mathematics - Putri Nur Aeni; Hanifah Nurus Sopiany; Nur Azizah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2026)
Mathematical literacy and mathematical reasoning are widely recognized as essential competencies for meaningful engagement with mathematics; however, the cognitive conditions shaping their relationship remain insufficiently understood. Drawing on Cognitive Load Theory, this study examined the association between mathematical literacy and mathematical reasoning and investigated whether Extraneous Cognitive Load (ECL) significantly moderates this association among Indonesian junior high school students. A quantitative ex post facto correlational design was employed involving 275 eighth-grade students selected through proportionate stratified random sampling. Data were collected using a mathematical literacy test, a mathematical reasoning test, and an ECL questionnaire adapted from the Cognitive Load Component Questionnaire. The data were analyzed using descriptive statistics, simple linear regression, and Moderated Regression Analysis (MRA). The findings revealed a significant positive association between mathematical literacy and mathematical reasoning, with mathematical literacy explaining 18.2% of the variance in mathematical reasoning (R² = .182). After the inclusion of Extraneous Cognitive Load and the interaction term, the explained variance increased to 19.4% (R² = .194), representing a modest increase in explanatory power (ΔR² = .012). Although ECL did not show a significant direct association with mathematical reasoning, the interaction between mathematical literacy and ECL was statistically significant and negative (β = −0.371, p = .048), indicating that higher levels of ECL were associated with a weaker positive association between mathematical literacy and mathematical reasoning. These findings provide empirical evidence that the association between mathematical literacy and mathematical reasoning varies according to students' perceived levels of Extraneous Cognitive Load and highlight the importance of fostering mathematical literacy while minimizing unnecessary extraneous cognitive demands to better support students' mathematical reasoning